Improving Reading Insights on Web Contents Based: A Survey on the Strategies Used by EFL Students - Risa Lestari; Syahdan Syahdan (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
Implementing strategies of content chosen on the internet is a core aspect of achieving goals in expanding reading material. This study aims to investigate what are the strategies used by students on extending reading web content. This research is in the form of a survey at the English Department, Faculty of Teacher Training and Education, Universitas Lancang Kuning. There were 95 out of 126 EFL students selected randomly as participants from reading class. A set of Likert-scale questionnaires, adopted from Mokhtari and Reichard (2002), was used to collect the data. It consisted of 30 questions divided into three strategies: Global Reading Strategies, Problem Solving Strategies, and Support Reading Strategies. To answer the research questions, descriptive statistics (SPSS 16) were used to analyze EFL students’ strategies on extending reading web content questionnaires. The findings reveal that students' dominant strategy is the Problem Solving Strategies got from the mean score of 4.11 and a Standard Deviation of 0.98. It can be categorized into a high level. It means that the majority of students have a homogenous strategy for extending reading web content. The study also reveals that students believe that the content on the internet somehow is the right source of learning. Therefore this study highlighted that students have implemented a reading strategy to make them easier to understand a text's contents.